2019
DOI: 10.1002/ams2.409
|View full text |Cite
|
Sign up to set email alerts
|

Successful support by veno‐arterial extracorporeal membrane oxygenation for severe septic shock caused by Aeromonas hydrophila

Abstract: Background Septic shock is a subset of sepsis accompanied by profound circulatory and cellular metabolism abnormalities. Although veno‐arterial extracorporeal membrane oxygenation (VA‐ECMO) can provide temporary cardiac support to improve organ perfusion, hemodynamic support by VA‐ECMO for adult patients with septic shock is still controversial. Case presentation A 67‐year‐old man was transferred to our hospital with generalized weakness. He suffered septic shock refractory to vasopressors and inotropes, and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Although intensive treatments including veno-arterial extracorporeal membrane oxygenation, T A B L E 2 Mortality analysis of patients with Aeromonas hydrophila isolation polymyxin B hemoperfusion, or cytokine-absorbing hemofiltration have been reported as successful for patients with A hydrophila sepsis, the effect might be limited. 17,18 Our mortality analysis showed that blood loss > 1000 mL might be a risk factor for mortality in patients with A hydrophila infection. However, massive blood loss has long been recognized as a risk factor for SSI.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Although intensive treatments including veno-arterial extracorporeal membrane oxygenation, T A B L E 2 Mortality analysis of patients with Aeromonas hydrophila isolation polymyxin B hemoperfusion, or cytokine-absorbing hemofiltration have been reported as successful for patients with A hydrophila sepsis, the effect might be limited. 17,18 Our mortality analysis showed that blood loss > 1000 mL might be a risk factor for mortality in patients with A hydrophila infection. However, massive blood loss has long been recognized as a risk factor for SSI.…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, the clinical course of these patients was rapid, and most of them died within 3 days after the onset. Although intensive treatments including veno‐arterial extracorporeal membrane oxygenation, polymyxin B hemoperfusion, or cytokine‐absorbing hemofiltration have been reported as successful for patients with A hydrophila sepsis, the effect might be limited 17,18 …”
Section: Discussionmentioning
confidence: 99%
“…We note that treatment an antimicrobial regimen comprising ABPC/SBT, customarily used to treat aspiration pneumonia, for several days was ineffective in achieving any significant improvement in his septic shock status due to infection with A. caviae . Therefore, due to the high mortality risk of Aeromonas sp.‐related respiratory infections, 1 , 2 , 3 fluoroquinolones and carbapenems should be started early if a near‐drowning incident is suspected. Moreover, in severe respiratory infections due to Aeromonas sp., antimicrobial agents should be switched or combined if there is no improvement, even if the susceptibility testing is favorable.…”
Section: Discussionmentioning
confidence: 99%
“…are rare, but the mortality rate is high. 1 , 2 , 3 We encountered a patient with septic shock due to infection with Aeromonas caviae , which he contracted during a near‐drowning accident in river water. In such cases, combination therapy should be considered when previously treatment with antimicrobial agents do not provide sufficient improvement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation